Effect of enzyme supplementation on nutritive values of fermented palm kernel cake used to substitute soybean meal in broiler diet - Sinurat, Arnold P.; Purwadaria, Tresnawati; Purba, Maijon (Indonesian Journal of Animal and Veterinary Sciences, 2015)
Two experiments was designed to improve nutritional values of palm kernel cake (PKC) by biofermentation process, followed by enzyme supplementation to substitute soybean meal (SBM) in broilers diet. A factorial of 2 x 2 design was applied in the first experiment, i.e. fermentation process (non fermented PKC and fermented PKC) and enzyme supplementation (no enzyme and +BS4 enzyme). Dry matter (DM) digestibility, AME and amino acids ileal digestibility (IAAD) of the treatment ingredients were measured in broiler chickens. Seven replications were applied for the DM and AME assays and 3 replications for IAAD assay. Second experiment was designed to study the effect of SBM substitution with enzyme supplemented FPKC (EFPKC). Four diets were formulated, i.e., control diet without EFPKC, 10%, 20 and 40% SBM substituted with EFPKC. All diets were formulated to meet the nutrient requirements of broilers. Each diet was fed to broilers from 1 to 35 d. Body weight, feed consumption, FCR and mortalities were measured. Carcass yield, abdominal fat and weight of liver and gizzard were measured at the end of experiment. Results showed that fermentation of PKC increased the DM digestibility, the AME was also increased but not significant. Enzyme supplementation did not affect the DM digestibility and AME of PKC. Fermentation process significantly (P<0.05) decreased IAAD of some indispensable amino acids. However, supplementation of enzyme did not affect the IAAD of indispensable amino acids. Substitution of soybean meal with EFPKC reduced the feed intake and growth rate of broilers. Key Words: Palm Kernel Cake, Fermentation, Enzyme, Broilers, Soybean Meal